2021
DOI: 10.3390/pathogens10080989
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax Genetic Diversity in Panama: Challenges for Malaria Elimination in Mesoamerica

Abstract: Panama and all nations within the Mesoamerican region have committed to eliminate malaria within this decade. With more than 90% of the malaria cases in this region caused by Plasmodium vivax, an efficient national/regional elimination plan must include a comprehensive study of this parasite’s genetic diversity. Here, we retrospectively analyzed P. vivax genetic diversity in autochthonous and imported field isolates collected in different endemic regions in Panama from 2007 to 2020, using highly polymorphic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The western region showed higher haplotype diversity indexes and outnumbered the eastern region in the number of haplotypes. Differences in genetic diversity at the haplotype level between these two regions have also been reported for Plasmodium vivax [37]. In the case of P. vivax, it was suggested that different ecological and climate conditions as well as vector diversity prevalent in both areas have influenced local malaria transmission and therefore the genetic structure of Plasmodium.…”
Section: Discussionmentioning
confidence: 89%
“…The western region showed higher haplotype diversity indexes and outnumbered the eastern region in the number of haplotypes. Differences in genetic diversity at the haplotype level between these two regions have also been reported for Plasmodium vivax [37]. In the case of P. vivax, it was suggested that different ecological and climate conditions as well as vector diversity prevalent in both areas have influenced local malaria transmission and therefore the genetic structure of Plasmodium.…”
Section: Discussionmentioning
confidence: 89%
“…Recent molecular studies have shown that P. falciparum parasites circulating in this eastern region are resistant to chloroquine and partially resistant to antifolates [ 21 , 22 , 23 ], a resistant profile not observed in P. falciparum parasites circulating in the rest of the Mesoamerican countries. It has also been described that malaria parasites from the eastern side have a higher genetic diversity [ 24 , 25 ], as well as a higher vector species richness [ 26 ]. The ecological conditions also differed, particularly in the amount and seasonal distribution of rainfall, mean annual temperatures, daily fluctuations in temperature, and landcover [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent use of this tool has been successful in Plasmodium vivax (P. vivax) investigations, to provide insight in genetic diversity in Panama [11] and for reconstruction of a malaria outbreak in a low transmission area [12]. In addition, PCR-RFLP has been utilized to assess the geographic origin of Plasmodium falciparum strains (P. falciparum) in Central America [3].…”
Section: Introductionmentioning
confidence: 99%